Korelasi antara Kemampuan Membaca dengan Kemampuan Komunikasi Matematis Taruna Akademi Maritim Cirebon - Yosi Adiputra; Handayani Eka Putri; Fathul Hidayati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This research aims to determine the extent of the relationship between reading ability and mathematical communication skills among cadets at the Cirebon Maritime Academy. The method used in this study is a quantitative approach with a correlational research design. The sample consisted of 35 cadets majoring in nautical sciences who were selected as research participants. Data were collected through two different instruments, namely a reading ability test and a mathematical communication ability test, which were administered at separate times to avoid bias. The obtained data were then analyzed using a correlation formula to examine the relationship between the two variables. The results of the data analysis showed a correlation coefficient of 0.722. Based on the interpretation criteria of correlation coefficients, this value falls into the high category. These findings indicate a strong positive relationship between reading ability and mathematical communication skills, meaning that cadets with higher reading ability tend to demonstrate better mathematical communication skills